Interaction in second language classrooms - Chowdhury, Shaheena (BRAC University, 2010)
Dealing with reticent students in a second language classroom is one the major issues a language teacher is faced with, and it becomes an exasperating experience when the students are from multicultural background who do not know how to respond to a teacher’s queries. Language teachers are confronted with the challenge of student-student and teacher-student interaction. In my paper I have explored the problem of active participation in an L2 classroom and sought to resolve how interaction takes place in formal instructional settings by incorporating the views of researchers and my own teaching experience.